2022
DOI: 10.12982/vis.2022.046
|View full text |Cite
|
Sign up to set email alerts
|

Dietary organic trace mineral supplement affects steroid hormone, antioxidant enzyme concentrations, and reproductive performances in dairy cows

Abstract: Supplementation of organic trace mineral (OTM) may affect reproductive functions in several aspects and has been studied, but very rare is reported in dairy cows. To determine the effects of dietary OTM supplement during pre- and postpartum with timed artificial insemination (TAI) protocol on steroid hormones, antioxidant enzymes, and reproductive performances in dairy cows. Prepartum Holstein cows (n = 60) were randomly assigned to received either a control diet or OTM supplemented for 42 days. Both groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As a more bioavailable source of trace minerals ( 22 ), OTMs are widely used in the production of pigs ( 12 , 23 ), broilers ( 24 , 25 ), laying hens ( 7 , 8 , 26 ), and dairy cows ( 27 , 28 ) for their performance-enhancing effects. However, studies on animals fed different trace mineral sources have yielded inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a more bioavailable source of trace minerals ( 22 ), OTMs are widely used in the production of pigs ( 12 , 23 ), broilers ( 24 , 25 ), laying hens ( 7 , 8 , 26 ), and dairy cows ( 27 , 28 ) for their performance-enhancing effects. However, studies on animals fed different trace mineral sources have yielded inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that OTMs have a higher digestibility and absorption rate compared with ITMs, which could improve SOD activity and reduce lipid oxidation ( 12 , 13 , 29 , 33 ). Cows fed diets containing OTMs had higher serum SOD and GSH-px activities than those fed diets containing the same amount of ITMs ( 28 ), and pigs fed diets supplemented with OTMs had higher hepatic Cu/Zn-SOD and GSH-px activities than those fed diets supplemented with ITMs ( 34 ). Feng et al ( 12 ) found that feeding diets supplemented with Fe-Gly could increase serum SOD activity in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Organic trace minerals supplementation has been linked to improve eggshell quality in poultry (Wang et al, 2019) and improve ruminant productive performances (Khanthusaeng et al, 2022). Se is an important microelement used in the diet of poultry that is used to maintain laying integrity (LI) and egg production (Elpawati et al, 2018).…”
Section: Introductionmentioning
confidence: 99%